2007
DOI: 10.1186/1471-2148-7-128
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of ribonuclease H genes in prokaryotes to avoid inheritance of redundant genes

Abstract: Background: A theoretical model of genetic redundancy has proposed that the fates of redundant genes depend on the degree of functional redundancy, and that functionally redundant genes will not be inherited together. However, no example of actual gene evolution has been reported that can be used to test this model. Here, we analyzed the molecular evolution of the ribonuclease H (RNase H) family in prokaryotes and used the results to examine the implications of functional redundancy for gene evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 60 publications
(71 reference statements)
1
67
0
Order By: Relevance
“…Phylogenetic reconstruction of bacterial evolution can be more straightforward than searches for protein orthologs, and this has been done for Firmicutes species in the past (15). We have reconstructed a Firmicutes phylogenetic tree that includes all known sspE-containing species, along with a number of other Firmicutes, including those of Bacillales species that lack an sspE gene.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic reconstruction of bacterial evolution can be more straightforward than searches for protein orthologs, and this has been done for Firmicutes species in the past (15). We have reconstructed a Firmicutes phylogenetic tree that includes all known sspE-containing species, along with a number of other Firmicutes, including those of Bacillales species that lack an sspE gene.…”
Section: Discussionmentioning
confidence: 99%
“…Data were compiled from (Zheng et al, 2015) and (Kochiwa et al, 2007). The y-axis represents the percent of genes on the chromosome that are co-oriented with respect to replication.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…DNA-damaging agents are known to have a profound effect on RNase HII activity (3,36). Although RNase H genes have evolved to avoid functional redundancy (25), it has been observed that the location and/or the activity of RNase H proteins may be influenced by other domains present on the same protein chain (10), indicating a possible interrelation between the RHII and RSD activities of MS_RHII-RSD. A basal level of (p)ppGpp is essential to destabilize RNA polymerases and maintain genomic integrity during DNA replication (54).…”
mentioning
confidence: 99%